Peperomin E Induces Apoptosis and Cytoprotective Autophagy in Human Prostate Cancer DU145 Cells In Vitro and In Vivo - Lin, Min; Zhu, Qiannan; Li, Yunzhi; Pan, Jigang (Planta Medica, 2021)
Peperomin E was first isolated from Peperomia dindygulensis, an anticarcinogenic herb, and exhibited anticancer activity in many cancer cell lines. To date, it is unknown whether peperomin E has an effect on human prostate cancer DU145 cells in vitro and in vivo. In this study, we used MTT to assess the proliferation inhibition activity of peperomin E in DU145 cells in vitro and observed the cell morphological changes by a phase contrast microscope. A DU145 cell xenograft tumor mouse model was used to evaluate the efficacy of peperomin E in vivo. Apoptosis rates were measured by flow cytometry, and protein expression levels were analyzed by western blot. The results showed that peperomin E significantly inhibited the proliferation of DU145 cells in vitro and reduced the weight and volume of tumors in vivo. Peperomin E also significantly induced the apoptosis and autophagic response of DU145 cells. The autophagic inhibitors LY294002 and chloroquine enhanced peperomin E-mediated inhibition of DU145 cell proliferation and induction of DU145 cell apoptosis. The results also showed that the Akt/mTOR pathway participated in peperomin E-induced autophagy in DU145 cells. In summary, our finding showed that peperomin E had an effect on DU145 cells in vitro and in a nude mouse DU145 cell xenograft model in vivo, demonstrated that peperomin E could significantly induce apoptosis and the autophagic response in DU145 cells and that autophagy played a cytoprotective role in peperomin E-treated DU145 cells. These results suggest that the combination of peperomin E treatment and autophagic inhibition has potential for the treatment of prostate cancer.
Keywords: Peperomia dindygulensis; Piperaceae; peperomin E; DU145 cell line; apoptosis; autophagy